Trismus: an unusual cause and its implications. (5th October 2020) - Greenstein, A.; Mistry, C.; Lees, R.; Lowe, T.
Abstract: Systemic diseases can manifest in many ways and subtle clues to these processes can often declare themselves in the maxillofacial region. This report highlights one usual and rare presentation of such case. A 64‐year‐old woman, presented to her general practitioner with worsening right‐sided jaw pain and trismus. She was referred to the local maxillofacial services and her mouth opening was measured at 1cm at presentation. An orthopantomogram (OPG) taken was unremarkable. She underwent an MRI of the head and neck that showed a soft tissue mass invading the right lateral and medial pterygoid muscles and plate with involvement of the ramus of the mandible. A staging CT was performed that revealed a mass of the proximal sigmoid colon. A colonoscopy performed with biopsy revealed a poorly differentiated squamous cell carcinoma with extensive metastasis, including the right masticatory space. She was presented at the multi‐disciplinary meeting where it was decided to treat her palliatively and she died 6 weeks after her diagnosis.